2017
DOI: 10.1039/c7ra07150g
|View full text |Cite
|
Sign up to set email alerts
|

Top-down synthesis of zinc oxide based inks for inkjet printing

Abstract: A top-down approach for synthesizing pure and doped inkjet printable metal oxide inks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 61 publications
1
37
0
Order By: Relevance
“…This approach gives an opportunity to control the shape, size, phase, and chemical composition and optical and structural properties of the nanomaterials that, in turn, regulate functional parameters of the final devices. To enhance the working parameters of the described devices, ink-jet printed nanocrystalline films can be subjected to thermal and chemical treatments [14].…”
Section: Introductionmentioning
confidence: 99%
“…This approach gives an opportunity to control the shape, size, phase, and chemical composition and optical and structural properties of the nanomaterials that, in turn, regulate functional parameters of the final devices. To enhance the working parameters of the described devices, ink-jet printed nanocrystalline films can be subjected to thermal and chemical treatments [14].…”
Section: Introductionmentioning
confidence: 99%
“…A vast variety of materials can be deposited by inkjet printing, including metallic nanoparticles and nanowires [3][4][5][6], polymers [7,8], semiconductors [9,10], quantum dots [11] and carbon nanotubes [12]. These materials are used to produce different types of electronic components such as lightemitting diodes [13], biosensors [14,15], supercapacitors [16], transistors [17,18], and solar cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…The transparent functional ink containing polysiloxane in the form of a micro-emulsion should have a particle size distribution between 1 and 100 nm. The stated particle size (15 nm) is considerably below 200 nm, which is an experienced particle size limitation to avoid agglomeration of particles in the printing nozzle channel [31]. The functional ink was able to filter through nylon syringe filters with pore sizes of 0.45 and 0.2 lm, respectively, which confirmed that the functional particles are compatible with the inkjet printing process.…”
Section: Resultsmentioning
confidence: 70%